Perancangan Dan Implementasi E-Commerce Pada Toko Pakaian Govind Store Berbasis Web Mobile - Risqi; Khusnul Khotimah (Fakultas Teknik Universitas Muhammadiyah Parepare, 2026)
The rapid advancement of information technology has accelerated digital transformation across various business sectors, including Micro, Small, and Medium Enterprises (MSMEs), through the adoption of electronic commerce (e-commerce) systems. Govind Store is a clothing retail business that still relies on conventional sales processes, resulting in ineffective product promotion, transaction management, and sales reporting. This study aims to design and implement a mobile web-based e-commerce system to improve sales management efficiency and expand market reach. The system was developed using the Waterfall software development methodology, which consists of the requirements analysis, system design, implementation, testing, and maintenance phases. The application was built using PHP Native, MySQL, and Bootstrap to provide a responsive interface across various mobile devices. System functionality was evaluated using Black Box Testing, and the results indicate that all core features, including user authentication, product management, shopping cart, checkout, payment, and sales reporting, operated according to the specified functional requirements. The implementation of the proposed system improves business process efficiency, facilitates online transactions for customers, and assists store administrators in managing sales data more accurately, efficiently, and in an integrated manner.